2021
DOI: 10.3389/fimmu.2021.621744
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture Expansion Shifts the Immune Phenotype of Human Adipose-Derived Mesenchymal Stem Cells

Abstract: Human mesenchymal stem or stromal cells (hMSCs) are known for their potential in regenerative medicine due to their differentiation abilities, secretion of trophic factors, and regulation of immune responses in damaged tissues. Due to the limited quantity of hMSCs typically isolated from bone marrow, other tissue sources, such as adipose tissue-derived mesenchymal stem cells (hASCs), are considered a promising alternative. However, differences have been observed for hASCs in the context of metabolic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 80 publications
(128 reference statements)
1
28
0
Order By: Relevance
“…Although renowned as MSC signature markers, the expression of CD73, CD90, CD105 and CD146 are far from uniform and their function in MSC biology is still little understood. Special attention needs to be paid to the sparse literature data from human native as opposed to the more common cultured MSC, as the expression of signature and functional markers appear to be donor-dependent or change during the ex vivo-manipulation of MSC [ 16 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although renowned as MSC signature markers, the expression of CD73, CD90, CD105 and CD146 are far from uniform and their function in MSC biology is still little understood. Special attention needs to be paid to the sparse literature data from human native as opposed to the more common cultured MSC, as the expression of signature and functional markers appear to be donor-dependent or change during the ex vivo-manipulation of MSC [ 16 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jeske et al found that ASCs were less susceptible to culture stress relative to BM-MSCs. An increased secretion of pro-inflammatory cytokines and decreased secretion of anti-inflammatory cytokines was observed after extended culture expansion of ASCs [68].…”
Section: Ascs From the Same Adipose Tissue Depotmentioning
confidence: 95%
“…However, ASC expansion on the flat layer of the plastic surface cannot accurately mimic the natural microenvironment for cell growth in vivo due to a lack of three-dimensional tissue structure information ( Yin et al, 2020 ). Furthermore, more evidence has shown that the extensive passage of ASCs in planar culture can cause cell morphology changes, leading to cell cycle arrest, induction of replication and senescence, and loss of differentiation potential ( Delben et al, 2021 ; Jeske et al, 2021 ). As a result, scientists are trying to find new cultivation methods that can overcome or partially overcome these problems, and 3D ASC culture is a novel approach.…”
Section: Introductionmentioning
confidence: 99%